Ruptured ovarian artery aneurysm in puerperium: a rare occurrence - Bajaj, Bindu; Bajaj, Sunil Kumar; Misra, Ritu; Gupta, Rohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We present a rare case of Ovarian Artery Aneurysm in a puerperium. It was managed by endocopic banding of the ovarian artery following failed attempts at endovascular embolisation. The patient remained stable on three months follow up. The pathogenesis of this rare condition is also discussed.